Long Noncoding RNA in Prostate, Bladder, and Kidney Cancer - Martens-Uzunova, Elena S.; Böttcher, René; Croce, Carlo M.; Jenster, Guido; Visakorpi, Tapio; Calin, George A. (European urology, 2014)
Genomic regions without protein-coding potential give rise to millions of protein-noncoding RNA transcripts (noncoding RNA) that participate in virtually all cellular processes. Research over the last 10 yr has accumulated evidence that long noncoding RNAs (lncRNAs) are often altered in human urologic cancers. To review current progress in the biology and implication of lncRNAs associated with prostate, bladder, and kidney cancer. The PubMed database was searched for articles in the English language with combinations of the Medical Subject Headings terms long non coding RNA, long noncoding RNA, long untranslated RNA, cancer, neoplasms, prostate, bladder, and kidney. We summarise existing knowledge on the systematics, biology, and function of lncRNAs, particularly these involved in prostate, kidney, and bladder cancer. We also discuss the possible utilisation of lncRNAs as novel biomarkers and potential therapeutic targets in urologic malignancies and portray the major challenges and future perspectives of ongoing lncRNA research. LncRNAs are important regulators of gene expression interacting with the major pathways of cell growth, proliferation, differentiation, and survival. Alterations in the function of lncRNAs promote tumour formation, progression, and metastasis of prostate, bladder, and kidney cancer. LncRNAs can be used as noninvasive tumour markers in urologic malignancies. Increased knowledge of the molecular mechanisms by which lncRNAs perform their function in the normal and malignant cell will lead to a better understanding of tumour biology and could provide novel therapeutic targets for the treatment of urologic cancers. In this paper we reviewed current knowledge of long noncoding RNAs (lncRNAs) for the detection and treatment of urologic cancers. We conclude that lncRNAs can be used as novel biomarkers in prostate, kidney, or bladder cancer. LncRNAs hold promise as future therapeutic targets, but more research is needed to gain a better understanding of their biologic function. Long noncoding RNAs (lncRNAs) are an integral part of cellular signalling, controlling cellular proliferation, differentiation, and survival. The functional impairment of lncRNAs is associated with carcinogenesis and cancer progression in urologic and other malignancies. LncRNAs hold clinical potential as novel biomarkers and therapeutics.